Performance of semi lightweight concrete composite deck slabs under falling mass. (August 2022) - Saketh Raman, K.; Bhuvaneshwari, P.
Abstract: In the present scenario probability of unexpected and accidental loading is high for the infrastructures. There is an urgent need to analyse these structures to check their viability against impact load. Composite structures are currently used to utilize the benefits of different materials. Past research works focused on the response of composite slabs under static load. Studies related to the impact response of composite slabs are limited, and the behaviour of less dense slabs is still to be explored. There is a demand to focus on the reaction of semi-lightweight aggregate concrete for composite grooved trapezoidal decking slabs subjected to drop mass impact. The study focused on the cushioning effect of six composite slab specimens (1000 mm × 930 mm × 80 mm) along with welded wire mesh and steel fibers as secondary reinforcements. Two were cast using control concrete (NC), and four were cast using lightweight concrete (LC). The collision was achieved by dropping a 55 kg steel cylinder to hit the center of the slab from a height of 1 m. Numerical modeling and analysis of similar slabs under impact load were carried out in ANSYS. The parameters concentrated are impacted force–time history, acceleration, crack pattern, bond-slip behaviour, and stress contours. The results show that lightweight concrete with welded wire mesh as secondary reinforcement could be effectively utilised as a cushioning layer for the composite deck system under falling mass scenarios.